Distributed Sensor Networks, 2nd Edition - Iyengar, S.; Brooks, Richard (Chapman and Hall/CRC, 2016)
The best-selling Distributed Sensor Networks became the definitive guide to understanding this far-reaching technology. Preserving the excellence and accessibility of its predecessor, Distributed Sensor Networks, Second Edition once again provides all the fundamentals and applications in one complete, self-contained source. Ideal as a tutorial for.
Online resource; Title from title page (viewed April 19, 2016)
Keywords: Sensor networks; Intelligent agents (Computer software); Multisensor data fusion; Réseaux de capteurs; Agents intelligents (Logiciels); Fusion multicapteurs